2011
DOI: 10.1038/onc.2011.562
|View full text |Cite
|
Sign up to set email alerts
|

Akt2 interacts with Snail1 in the E-cadherin promoter

Abstract: Snail1 is a transcriptional factor essential for triggering epithelial-to-mesenchymal transition. Moreover, Snail1 promotes resistance to apoptosis, an effect associated to PTEN gene repression and Akt stimulation. In this article we demonstrate that Snail1 activates Akt at an additional level, as it directly binds to and activates this protein kinase. The interaction is observed in the nucleus and increases the intrinsic Akt activity. We determined that Akt2 is the isoform interacting with Snail1, an associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
(79 reference statements)
1
27
0
Order By: Relevance
“…90 The pro-metastatic properties of Akt2 may reside in its capacity to regulate the activity of Twist1 and Snail1, 2 classical EMT-TFs. 91,92 Expression of both Twist1 and Akt2 was found to be elevated in highly invasive breast cancer cells, 91 and silencing of Akt2 decreased Twist1-induced migration and invasion. Moreover, Twist1 was found to bind E-box elements in the Akt2 promoter and thereby enhance its expression.…”
Section: Smad and Non-smad Signaling In Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…90 The pro-metastatic properties of Akt2 may reside in its capacity to regulate the activity of Twist1 and Snail1, 2 classical EMT-TFs. 91,92 Expression of both Twist1 and Akt2 was found to be elevated in highly invasive breast cancer cells, 91 and silencing of Akt2 decreased Twist1-induced migration and invasion. Moreover, Twist1 was found to bind E-box elements in the Akt2 promoter and thereby enhance its expression.…”
Section: Smad and Non-smad Signaling In Emtmentioning
confidence: 99%
“…Silencing of Akt2 prevents Snail-induced downregulation of Ecadherin. 92 Finally, Iliopoulos and colleagues showed that the miR-200a family regulates E-cadherin repression and EMT. 93 The amount of miR-200a present in a cell was shown to be dependent on the balance between Akt1 and Akt2 expression.…”
Section: Smad and Non-smad Signaling In Emtmentioning
confidence: 99%
“…Specific phosphorylation of palladin, an actin bundling protein, by Akt1 led to decreased migration (10). Conversely, Akt2 has been found to promote breast cancer epithelial to mesenchymal transition (EMT) through miR-200 modulation (11) as well as an interaction with Snail1 on the E-cadherin promoter (12). Functional differences in glioma have been slightly variable by using knockdown systems in transformed cells.…”
mentioning
confidence: 99%
“…In any case, this specific Akt2 subnuclear localization might facilitate its action on FoxO1 and GSK-3␤, promoting the inactivation of this kinase and the subsequent stabilization of Snail1. Since Snail1 also interacts with and increases Akt2 activity (43), it is possible that it creates a stimulatory loop to further enhance Akt2 activity on nuclear targets that regulate apoptosis. In any case, our results explain how Snail1 is controlled by Notch to regulate EndMT and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Coverslips were incubated with pGSK-3␤ (S9) at 1:50 in blocking buffer (PBS-3% BSA) and rinsed with PBS. To detect Akt1 and Akt2 in the nuclear compartment without cytoplasmic interference, the cells were pretreated with CSK buffer as previously described (43) and analyzed with antibodies against Akt1, Akt2, and lamin B (1:50). Briefly, coverslips were incubated on ice for 5 min with CSK buffer (20 mM HEPES [pH 8], 100 mM KCl, 3 mM MgCl 2 , 300 mM sucrose) containing 0.5% Triton X-100 and rinsed once with CSK buffer without Triton X-100.…”
Section: Methodsmentioning
confidence: 99%